The Use of Musical Elements in Music Learning as an Effort to Foster Creativity of Children - Kwidura, Nugroho; Utomo, Udi; Wadiyo, Wadiyo (Catharsis, 2021)
The purpose of this study is to explain and reveal how the process of using musical elements is applied as an effort to foster creativity of the students in Foundation of Music class at Sekolah Musik Indonesia Semarang. This research used an interdisciplinary approach with qualitative analytical methods. The research design used a case study and the focus of the research was the Foundation of Music class at Sekolah Musik Indonesia Semarang. The data collection techniques used were observation, interviews and documentation studies. Validation of data in this study used triangulation techniques and data analysis techniques used interactive models. The results of this study show that the first process of using musical elements in classroom learning of Foundation of Music is able to introduce elements of music (rhythm and melody) using the sequence/order of learning set at the Foundation of Music class and also by using play-based learning method and learning media in the form of musical instruments, puzzles music books, and paper notation used during the process learning takes place. Second, the activities carried out during the learning process lead to a creative process through the teacher's openness and its positive impact on the students (creative personality), integration of methods and diversity of learning activities (creative process), and verbal motivation (creativity press).